Integrated adsorption-photocatalytic degradation of chicken processing wastewater using powdered activated carbon-supported graphitic carbon nitride - Sim, Lan Ching; Leong, Ken Lap; Chong, Woon Chan; Leong, Kah Hon; Chin, Yik Heng; Saravanan, Pichiah; Azrina, Abd Aziz (Taylor's University, 2024)
Due to the expansion of agricultural sector, a massive volume of chicken processing wastewater has been produced and the conventional technologies are ineffective to remove organic and inorganic compounds. Thus, this work investigates the performance for the adsorption-photocatalytic degradation of chicken processing wastewater using powdered activated carbon (AC) supported on different weightage of graphitic carbon nitride (g-C3N4) (20 wt%, 40 wt% and 60 wt%). The AC was successfully combined with g-C3N4 by pyrolyzing the urea and AC mixture. The presence of AC reduced the agglomeration of g-C3N4 by providing a larger surface area to trigger more active sites. AC achieved the highest chemical oxygen demand (COD) adsorption efficiency (79.00 %) whereas the pure g-C3N4 showed the strongest adsorption capacity for orthophosphate (49.10 %) and ammonia nitrogen (NH3-N) (100 %). This proves that the microporous structure of AC was not suitable to remove orthophosphate and NH3-N. The highest photodegradation efficiency of COD (47.00 %), orthophosphate (49.00 %) and NH3-N (52.90 %) was successfully achieved by 20 wt% g-C3N4/AC, g-C3N4 and 60 wt% g-C3N4/AC, respectively. Overall, 98.20 % of COD, 98.10 % of orthophosphate and 100% of NH3-N was removed using integrated adsorption-photocatalytic degradation, making this technique a feasible method for on-site chicken processing wastewater treatment.